Trançando o cotidiano: uma abordagem sobre a produção de cestaria Guarani Mbya - Fazanaro, Tainá Rabatini (Universidade Federal de São Carlos, 2020)
This research introduces an approach about the Guarani Mbya's basketry production universe, from the indigenous land Boa Vista do Sertão do Prumirim, located on Ubatuba, at the north coast of the state of São Paulo. I begin this work with a discussion about the creation of the world and the construction of the body and the person Guarani Mbya. To make, from this, considerations about the basketry handmade production. The purpose was to comprehend how the basketry production can tell us about the relations between humans and not humans, people and objects, about indigenous and not indigenous. Relationships that are generated during this process of making. The women of the village are the main agents inside this relationship network. When they get together to braid their baskets, these women tell us, through the graphic patterns, the use of colours and shapes that weave in the taquara, about the mythical narratives about the creation of the world and the differences of origin between Mbya and juruá. The women and their baskets, figure as “chroniclers of reality”, weaving together the daily life of the village
Braiding the daily life: an approach on the production of basketry Guarani Mbya
Keywords: Guarani Mbya; Etnologia; Cestaria; Antropologia da arte; Ethnology; Basketry; Anthropology of art; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA